Curable resin composition, dry film and cured product thereof, and electronic component comprising the cured product

By using a curable resin composition of amideimide resin, thermosetting resin, heat curing accelerator and inorganic particles, the problem of coloring of the curable resin composition in the dry film and cured product is solved, and excellent heat resistance is achieved , low warpage and high light transmittance.

CN114269857BActive Publication Date: 2025-02-25TAIYO HOLDINGS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080058929.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-09-02
Publication Date
2025-02-25
Estimated Expiration
2040-09-02

AI Technical Summary

Technical Problem

The conventional curable resin composition is prone to coloring problems of slightly yellow or slightly reddish brown in the dry film and cured substance, and is insufficient in heat resistance, light transmittance and warping.

Method used

A curable resin composition containing an amideimide resin, a thermosetting resin, a heat curing accelerator and inorganic particles is used to form a cured product with excellent heat resistance and low warpage through specific reaction conditions and component ratios.

Benefits of technology

Excellent heat resistance, low warpage and high light transmittance of cured substances are achieved, especially in the interlayer insulating materials and re-wiring insulating materials of printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003512255910000041
    Figure BDA0003512255910000041
Patent Text Reader

Abstract

[Subject] To provide: a curable resin composition having excellent heat resistance, low warpage, and further improved light transmittance of a cured product, a dry film and a cured product thereof, and an electronic component comprising the cured product. [Solution] A curable resin composition, a dry film and a cured product thereof, and an electronic component comprising the cured product are obtained, wherein the curable resin composition is characterized in that it comprises: (A) an amide-imide resin, (B) a thermosetting resin, (C) a thermosetting accelerator, and (D) inorganic particles, wherein (A) the amide-imide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 1000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable resin composition, for example, a curable resin composition for an interlayer insulating material used in rewiring of a printed wiring board, a dry film and a cured product thereof, and an electronic component including the cured product. Background Art

[0002] Conventionally, various properties such as heat resistance of the cured product have been improved by using a curable composition containing, for example, epoxy resin and phenol resin as thermosetting components as an interlayer insulating material for a printed circuit board (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2001-226464 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] However, as in Patent Document 1, when a phenolic resin is used, yellowish or reddish brown coloring can be seen in the curable resin composition, its dry film and cured product. It is believed that this is due to the yellowish or reddish brown coloring originally possessed by the phenolic resin. In addition, when a polyimide resin is used, when the polyimide skeleton has an aromatic ring, similarly to the case of using a phenolic resin, yellowish or reddish brown coloring can be seen in the curable resin composition, its dry film and cured product.

[0008] Therefore, an object of the present invention is to provide a curable resin composition having excellent heat resistance and low warpage and capable of further improving the light transmittance of a cured product, a dry film containing the same, a cured product thereof, and a printed wiring board containing the cured product.

[0009] Solutions for solving problems

[0010] The present inventors have conducted intensive studies in view of the above-mentioned purpose, and as a result, have found a curable resin composition characterized by comprising:

[0011] (A) amide-imide resin,

[0012] (B) Thermosetting resin,

[0013] (C) a thermal curing accelerator, and

[0014] (D) Inorganic particles,

[0015] The (A) amideimide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 1000. The present invention has been completed so far.

[0016] In the curable resin composition of the present invention, the (B) thermosetting resin is preferably an epoxy compound having a biphenyl skeleton, an epoxy compound having a dicyclopentadienyl skeleton, or a mixture thereof.

[0017] The curable resin composition of the present invention preferably has a light transmittance of 95% or more at 450 nm when formed into a cured coating film having a film thickness of 20 μm.

[0018] Furthermore, the curable resin composition of the present invention preferably has a residual stress of less than 25 MPa when formed into a cured coating film.

[0019] Furthermore, other objects of the present invention are achieved by a dry film, a cured product thereof, and an electronic component including the cured product, the dry film comprising a resin layer composed of the curable resin composition.

[0020] Effects of the Invention

[0021] According to the curable resin composition of the present invention, the cured product thereof has excellent heat resistance and low warpage, and further, the cured product thereof also has excellent light transmittance. DETAILED DESCRIPTION

[0022] The curable resin composition of the present invention comprises: (A) an amide-imide resin, (B) a thermosetting resin, (C) a thermosetting accelerator, and (D) inorganic particles, wherein the amide-imide resin (A) is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 1000.

[0023] The curable resin composition of the present invention has the above-mentioned structure, so that its cured product has excellent heat resistance and low warpage, and further, its cured product has good light transmittance, especially visible light transmittance. In addition, the curable composition of the present invention has good lamination properties, and the residual stress of the cured product is suppressed.

[0024] That is, the curable resin composition of the present invention exhibits good heat resistance by curing and can suppress the occurrence of warping. Therefore, it is meaningful in applications such as interlayer insulating materials for printed wiring boards and insulating materials for redistribution, especially in applications where a low level of colorability is desired.

[0025] Hereinafter, each constituent component of the curable resin composition will be described in detail.

[0026] [(A) Amide-imide resin]

[0027] The curable resin composition of the present invention contains (A) an amideimide resin.

[0028] (A) amide-imide resin can be produced by reacting an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure with a tricarboxylic anhydride having an aliphatic structure, and a number average molecular weight of 500 to 1000 is used. That is, the (A) amide-imide resin used in the present invention forms an imide bond directly from the above-mentioned isocyanurate-type polyisocyanate and tricarboxylic anhydride, so that compared with the synthesis through a polyamic acid intermediate in the prior art, the stability, reproducibility and solubility of the material are good, and an amide-imide resin with excellent transparency can be synthesized. In addition, by making the number average molecular weight of the (A) amide-imide resin in the range of 500 to 1000, it becomes a relatively low viscosity, easy to disperse, the melt viscosity during lamination is reduced, and the lamination property is also improved. In addition, the heat resistance of the curable composition is improved by the imide skeleton possessed by the (A) amide-imide resin. Isocyanurate-type polyisocyanate and tricarboxylic anhydride are structures that do not have an aromatic ring structure. The amideimide resin of the present invention thus obtained has high transparency, and further, a cured product obtained from the curable resin composition of the present invention containing the amideimide resin also has high transparency.

[0029] [Isocyanurate type polyisocyanate]

[0030] The above-mentioned isocyanurate type polyisocyanate which is a synthetic raw material of the (A) amideimide resin is synthesized from aliphatic isocyanurate, that is, aliphatic linear isocyanate (for example, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate) or alicyclic isocyanate (isophorone diisocyanate, hydrogenated toluene diisocyanate, hydrogenated xylene diisocyanate, norbornane diisocyanate, hydrogenated diphenylmethane diisocyanate).

[0031] Specific examples of isocyanurate type polyisocyanates are:

[0032] HDI3N: Isocyanurate type triisocyanate synthesized from hexamethylene diisocyanate,

[0033] HTMDI3N: Isocyanurate type triisocyanate synthesized from trimethylhexamethylene diisocyanate,

[0034] IPDI3N: Isocyanurate-type triisocyanate synthesized from isophorone diisocyanate,

[0035] HTDI3N: Isocyanurate-type triisocyanate synthesized from hydrogenated toluene diisocyanate,

[0036] HXDI3N: isocyanurate triisocyanate synthesized from hydrogenated xylene diisocyanate, NBDI3N: isocyanurate triisocyanate synthesized from norbornane diisocyanate, and

[0037] HMDI3N: Isocyanurate-type triisocyanate synthesized from hydrogenated diphenylmethane diisocyanate.

[0038] The above-mentioned triisocyanurates may be used alone or in combination.

[0039] The isocyanate used as the raw material of the amide-imide resin (A) is preferably an alicyclic isocyanate, and isophorone diisocyanate is particularly preferred. By using an alicyclic isocyanate, the Tg of the amide-imide resin (A) is improved, and a cured coating film having particularly excellent thermal properties and transparency can be obtained from a curable resin composition containing the alicyclic isocyanate.

[0040] [Aliphatic tricarboxylic anhydride]

[0041] Examples of aliphatic tricarboxylic anhydrides as other reaction materials of the amideimide resin (A) include alicyclic tricarboxylic anhydrides such as cyclohexane tricarboxylic anhydride, methylcyclohexane tricarboxylic anhydride, cyclohexene tricarboxylic anhydride, and methylcyclohexene tricarboxylic anhydride. Cyclohexane tricarboxylic anhydride is particularly preferably used.

[0042] Cyclohexanetricarboxylic anhydride is preferably represented by the following formula (1):

[0043]

[0044] Specific examples thereof include cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride, cyclohexane-1,3,5-tricarboxylic acid-3,5-anhydride, cyclohexane-1,2,3-tricarboxylic acid-2,3-anhydride, and particularly cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride.

[0045] That is, by using such an aliphatic tricarboxylic acid anhydride as a raw material of the (A) amideimide resin, the heat resistance of the cured product of the present invention is further improved.

[0046] In addition, as the raw material for producing the amideimide resin (A), in addition to the above-mentioned aliphatic tricarboxylic acid anhydride, a bifunctional dicarboxylic acid compound such as an aliphatic or aromatic dicarboxylic acid, such as sebacic acid, phthalic acid, fumaric acid, maleic acid and anhydrides thereof may be used in combination as appropriate.

[0047] When the carboxylic acid component of the above-mentioned tricarboxylic anhydride reacts with the isocyanate component in the isocyanurate type polyisocyanate, imide and amide are formed, and the resin of the present invention becomes an amide-imide resin. In addition, when the isocyanurate type polyisocyanate is reacted with the tricarboxylic anhydride, an imide bond is formed by the anhydride group and the isocyanate group, and an amide bond is formed by the carboxyl group and the isocyanate group. However, when the tricarboxylic anhydride group and the polyisocyanate group are reacted at a ratio such that the carboxylic acid (carboxyl) component of the tricarboxylic anhydride remains, the obtained polyamide-imide resin becomes carboxyl. The carboxyl group reacts with the polymerizable groups such as the epoxy group of the epoxy resin contained in the curable resin composition of the present invention described later to form a cross-linked structure of the cured product. It should be noted that in the reaction of the tricarboxylic anhydride with the triisocyanate, the above-mentioned two reactions of amidation and imidization are considered, but the reaction rate of imidization is fast, so the tricarboxylic acid selectively forms an imide at the anhydride group.

[0048] When the isocyanurate type polyisocyanate synthesized from an isocyanate having an aliphatic structure is reacted with a tricarboxylic anhydride having an aliphatic structure in such a manner that the ratio [(M1) + (M2)) / (N)] of the total molar number of the carboxyl group (M1) and the molar number of the acid anhydride group (M2) of the tricarboxylic anhydride having an aliphatic structure to the molar number of the isocyanate group (N) of the isocyanurate type polyisocyanate synthesized from the isocyanate having an aliphatic structure is 1.1 to 3, it is preferred for the reasons that the polarity in the reaction system becomes high, the reaction proceeds smoothly, the isocyanate group does not remain, the stability of the obtained polyimide resin is good, the residual amount of tricarboxylic anhydride is also small, and it is not easy to cause separation problems such as recrystallization. Among them, 1.2 to 2 are more preferred. It should be noted that the acid anhydride group in the present invention refers to a -CO-O-CO- group obtained by intramolecular dehydration condensation of two carboxylic acid molecules.

[0049] The imidization reaction is preferably carried out as follows: in a solvent or in the absence of a solvent, one or more isocyanates having an aliphatic structure are mixed with one or more tricarboxylic anhydrides, and the temperature is raised while stirring. The reaction temperature is preferably 50°C to 250°C, particularly preferably 70°C to 180°C. By setting such a reaction temperature, the reaction rate is accelerated, and side reactions and decomposition are less likely to occur. In the reaction, anhydride groups and isocyanate groups form imide groups while decarboxylation is accompanied. The progress of the reaction can be tracked by analytical methods such as infrared spectroscopy, acid value, and quantitative analysis of isocyanate groups. In the infrared spectrum, 2270cm-1, which is the characteristic absorption of the isocyanate group, isocyanate group -1 It also decreases with the reaction, and then at 1860cm -1 and 850cm -1 On the other hand, the anhydride group with characteristic absorption at 1780 cm -1 and 1720cm -1The absorption of the imide group at the reaction site increases. The reaction can be terminated by lowering the temperature while confirming the target acid value, viscosity, molecular weight, etc. However, from the perspective of stability over time, it is more preferred to continue the reaction until the isocyanate group disappears. In addition, during and after the reaction, a catalyst, antioxidant, surfactant, other solvent, etc. can be added within the range that does not damage the physical properties of the synthesized resin.

[0050] The acid value of the amideimide resin of the present invention is preferably 70 to 210 KOHmg / g, particularly preferably 90 to 190 KOHmg / g. When it is 70 to 210 KOHmg / g, excellent performance as a cured property is exhibited.

[0051] The amideimide resin of the present invention is preferably soluble in the polar solvent containing neither nitrogen nor sulfur atoms. Examples of such amideimide resins include branched amideimide resins having a branched structure and an acid value of 60 KOHmg / g or more.

[0052] The number average molecular weight Mn of the amideimide resin (A) in the curable resin composition is 500 to 1,000, and preferably within the range of 700 to 900.

[0053] In the present invention, the number average molecular weight Mn of the amideimide resin (A) is 500 or more, so that the heat resistance of the cured coating film becomes good. The number average molecular weight Mn is 1000 or less, so that it becomes a low viscosity and is easy to disperse. The melt viscosity during lamination is reduced, and the lamination property becomes good.

[0054] In addition, in the present invention, the number average molecular weight is based on the measurement result of gel permeation chromatography (GPC) using a polystyrene standard unless otherwise specified.

[0055] The content of the amide-imide resin (A) is preferably in the range of 30 to 85% by mass, particularly preferably in the range of 40 to 70% by mass, relative to the total mass of the solid content of the curable resin composition. This is because by setting the blending amount in this range, the Tg of the curable resin composition is improved, and a cured coating film with excellent thermal properties can be obtained.

[0056] [(B) Thermosetting resin]

[0057] The curable resin composition of the present invention further contains (B) a thermosetting resin.

[0058] As (B) thermosetting resin, for example, epoxy compounds, oxetane compounds, episulfide compounds, especially those having two or more cyclic ether groups and / or cyclic sulfide groups in one molecule, multifunctional epoxy compounds, oxetane compounds, and episulfide resins can be used. Furthermore, known thermosetting resins such as (blocked) isocyanate compounds, especially polyisocyanate compounds having two or more isocyanate groups or blocked isocyanate groups in one molecule, melamine resins, amine resins such as benzoguanamine resins and their derivatives, bismaleimide, oxazine, cyclic carbonate compounds, and carbodiimide resins can also be cited. In the present invention, epoxy compounds are preferably used, and multifunctional epoxy compounds are particularly preferably used. The (A) amide-imide resin of the present invention has a carboxyl group, and reacts with the above-mentioned epoxy compound to alleviate the residual stress generated during curing. Therefore, when a cured coating film of the curable resin composition of the present invention is formed on a substrate, the warping of the substrate can be suppressed.

[0059] The epoxy resin used can be in liquid, solid or semi-solid state. Examples of the polyfunctional epoxy compound include bisphenol A type epoxy resins; brominated epoxy resins; novolac type epoxy resins; bisphenol F type epoxy resins; hydrogenated bisphenol A type epoxy resins; glycidylamine type epoxy resins; hydantoin type epoxy resins; alicyclic epoxy resins; trihydroxyphenylmethane type epoxy resins; dixylenol type or diphenol type epoxy resins or mixtures thereof; bisphenol S type epoxy resins; bisphenol A novolac type epoxy resins; tetrahydroxyphenylethane type epoxy resins; heterocyclic epoxy resins; diglycidyl phthalate resins; tetraglycidyl ditoluoylethane resins; naphthyl-containing epoxy resins; epoxy resins having a dicyclopentadiene skeleton; glycidyl methacrylate copolymerized epoxy resins; copolymerized epoxy resins of cyclohexylmaleimide and glycidyl methacrylate; epoxy-modified polybutadiene rubber derivatives; CTBN-modified epoxy resins, etc., but are not limited to these. Preferred epoxy resins include bisphenol A or bisphenol F novolac epoxy resins, bixylenol epoxy resins, biphenol epoxy resins, biphenol novolac epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins (eg, biphenyl aralkyl epoxy resins), and mixtures thereof.

[0060] From the viewpoint of improving heat resistance, an epoxy resin having an aromatic ring skeleton (for example, a biphenyl skeleton) is preferred, and from the viewpoint of improving transmittance, an epoxy resin having a dicyclopentadiene skeleton is preferred.

[0061] As the epoxy resin with aromatic ring skeleton, for example, epoxy resin with naphthalene skeleton, especially epoxy resin with aralkyl type naphthalene skeleton and epoxy resin with biphenyl skeleton, especially biphenyl aralkyl type epoxy resin can be cited. Wherein, for the epoxy resin with naphthalene skeleton, naphthalene is a planar structure, which reduces the linear expansion coefficient of the cured product and can further improve heat resistance. As the commercially available product of the epoxy resin with naphthalene skeleton, for example, ESN-190, ESN-360, EPICRON HP-4032, EPICRON, HP-4032D made by Nippon Steel Chemical, and NC-7000L made by Nippon Kayaku Co., Ltd. can be cited. The epoxy resin with biphenyl skeleton can also improve the heat resistance and low linear expansion of the cured product of the composition comprising it. Examples of commercially available products of the epoxy resin having a biphenyl skeleton include NC-3000, NC-3000-L, NC-3000-H, NC-3001, and NC-2000-L manufactured by Nippon Kayaku Co., Ltd.

[0062] Furthermore, as an epoxy resin having an alicyclic skeleton, for example, an epoxy resin having a dicyclopentadiene skeleton can be cited. The epoxy resin having an alicyclic skeleton can also be expected to have an improved effect on the glass transition temperature compared to the epoxy resin having a chain skeleton. Examples of commercially available products of epoxy resins having a dicyclopentadiene skeleton include: EPICLON (registered trademark) HP-7200, HP-7200-H, HP-7200-L manufactured by DIC Corporation, and XD-1000 manufactured by Nippon Kayaku Co., Ltd.

[0063] The thermosetting resins described above may be used alone or in combination of two or more.

[0064] When (B) a thermosetting resin is used, the amount thereof is 20 to 60 parts by mass, particularly 30 to 50 parts by mass, based on 100 parts by mass of the solid content of the curable resin composition. This allows the cured product of the curable resin composition to have extremely excellent heat resistance, low residual stress, and low warpage.

[0065] [(C) Thermal curing accelerator]

[0066] As the (C) heat curing accelerator used in the present invention, it can be arbitrarily selected from tertiary amines, tertiary amine salts, quaternary onium salts, tertiary phosphines, imidazole derivatives or crown ether complexes (for example, 18-crown-6 / potassium benzyl alcohol, potassium anisole, KCl, KBr, ammonium acetate, etc.), and they can be used alone or mixed with two or more. In addition, phosphorus ylide and the like can also be used. As tertiary amines, triethylamine, tributylamine, DBU (1,8-diazabicyclo [5.4.0] undecane-7-ene), DBN (1,5-diazabicyclo [4.3.0] non-5-ene), DABCO (1,4-diazabicyclo [2.2.2] octane), pyridine, N,N'-dimethyl-4-aminopyridine, etc. As tertiary amine salts, for example, U-CAT series manufactured by San-Apro Ltd. can be cited. Furthermore, quaternary onium salts formed by the addition reaction of tertiary amines or tertiary phosphines with carboxylic acids or strongly acidic phenols can also be used as reaction accelerators. They can be any method for forming quaternary salts before being added to the reaction system, or separately added to the reaction system for quaternary salt formation. Specifically, tributylamine acetate obtained from tributylamine and acetic acid, triphenylphosphine acetate formed from triphenylphosphine and acetic acid, etc. can be cited. As quaternary onium salts, ammonium salts, phosphonium salts, arsenic salts, antimonium salts, oxonium salts, sulfonium salts, selenium salts, tinium salts, iodonium salts, etc. can be cited. Particularly preferred are quaternary ammonium salts and quaternary phosphonium salts. As specific examples of quaternary ammonium salts, tetra-n-butylammonium chloride (TBAC), tetra-n-butylammonium bromide (TBAB), tetra-n-butylammonium iodide (TBAI), and tetra-n-butylammonium acetate (TBAAc) can be cited. As specific examples of quaternary phosphonium salts, tetra-n-butylphosphonium chloride (TBPC), tetra-n-butylphosphonium bromide (TBPB), tetra-n-butylphosphonium iodide (TBBI), tetraphenylphosphonium chloride (TPPC), tetraphenylphosphonium bromide (TPPB), tetraphenylphosphonium iodide (TPPI), ethyltriphenylphosphonium bromide (ETPPB), ethyltriphenylphosphonium acetate (ETPPAc), etc. can be cited. As tertiary phosphine, it is sufficient to be a trivalent organic phosphorus compound having an alkyl group or an aryl group with 1 to 12 carbon atoms. As specific examples, triethylphosphine, tributylphosphine, triphenylphosphine, etc. can be cited. As imidazole derivatives, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, etc. can be cited. Specific commercially available products include, for example, Curezol 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ, and 2E4MZ manufactured by Shikoku Chemical Industry Co., Ltd.And, as the product realizing the improvement of stability over time, Novocure HX-3721, HX-3748, HX-3741, HX-3088, HX-3722, HX-3742, HX-3921HP, HX-3941HP, HX-3613 etc. made by ASAHI-CIBA Ltd. can also be enumerated. As phosphorus ylide, as long as it is the compound obtained by the reaction of phosphonium salt and alkali, known material can be used, but from the ease of operation, the material with high stability is preferred. Specific examples include (formylmethylene)triphenylphosphine, (acetylmethylene)triphenylphosphine, (pivaloylmethylene)triphenylphosphine, (benzoylmethylene)triphenylphosphine, (p-methoxybenzoylmethylene)triphenylphosphine, (p-methylbenzoylmethylene)triphenylphosphine, (p-nitrobenzoylmethylene)triphenylphosphine, (naphthoyl)triphenylphosphine, (methoxycarbonyl)triphenylphosphine, (diacetylmethylene)triphenylphosphine, (acetylcyano)triphenylphosphine, and (dicyanomethylene)triphenylphosphine.

[0067] (C) The amount of the heat curing accelerator used is, for example, 0.1 to 25 mol%, more preferably 0.5 to 20 mol%, and more preferably 1 to 15 mol%, relative to 1 mol of the epoxy group. By using the amount of the curing accelerator in an amount of 0.1 mol% or more relative to the epoxy group, the reaction is easily carried out at a practical speed. On the other hand, from the perspective of the reaction promotion effect and economic efficiency, it is usually set to 25 mol% or less.

[0068] [(D) Inorganic particles]

[0069] The curable resin composition of the present invention contains (D) inorganic particles.

[0070] Specific examples include non-metal fillers such as silicon dioxide, barium sulfate, calcium carbonate, silicon nitride, aluminum nitride, boron nitride, aluminum oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, titanium oxide, mica, talc, Neuburg silica, and organic bentonite, and (D) inorganic particles such as copper, gold, silver, palladium, and silicon.

[0071] In the curable resin composition of the present invention, these (D) inorganic particles may be used alone or in combination of two or more. In the present invention, it is preferred to use barium sulfate, silicon dioxide, or both thereof.

[0072] For the average particle size of (D) inorganic particles, in order to make the cured product transparent and visible, the particle size can be less than 1 / 2 of the wavelength of visible light, which is less than 200nm, preferably less than 150nm, and more preferably less than 100nm. In the use of the curable resin composition of the present invention and its cured product, it is preferred that the cured product is transparent or close to transparent, and therefore, inorganic particles with an average particle size of less than 200nm are generally used. In order to obtain a non-colored transmission color, it is preferred that the average particle size of the inorganic particles is less than 100nm. That is, the smaller the average particle size, the more visible light is transmitted, and the (D) inorganic particles absorb the light in the visible region that needs to be colored, and transmit the light outside the visible light region, so that the (D) inorganic particles become transparent.

[0073] Here, the average particle size is a value measured by a laser diffraction method. Examples of a measuring device based on the laser diffraction method include a device manufactured by Nikkiso Co., Ltd. (Nanotrac wave) and the like.

[0074] In addition, when measuring the average particle size of inorganic particles in the solidified material, first, the surface of the solidified material is etched by plasma treatment to form a state where inorganic particles are visible, and then the inorganic particles are observed using a SEM (scanning electron microscope). In order to obtain the average particle size of the inorganic particles, the average particle size of the inorganic particles is measured at 1 μm. 2 The diameter of the inorganic particles observed within the range of , including other parts, is performed 5 times in the interior, and the average diameter of the inorganic particles can be calculated. Plasma treatment is, for example, as follows: As an apparatus, MARCH PLASMA SYSTEM INC AP-1000 is used, the power is set to 500W, the pressure is set to 300Torr, the gas is set to Ar, and the treatment time is set to 10 minutes.

[0075] The content of these (D) inorganic particles is 5 to 60% by mass, particularly preferably 10 to 50% by mass, relative to the total solid content of the curable resin composition of the present invention. The amount of the inorganic particles (D) can be appropriately selected according to the type of the inorganic particles, thereby improving heat resistance without reducing the transparency of the cured coating film.

[0076] In the resin composition of the present invention, when silicon dioxide is used as the inorganic particles (D), the surface of the inorganic particles treated with a silane coupling agent can be used. This is because precipitation and aggregation after dispersion in a liquid can be prevented, resulting in excellent storage stability. In addition, this is because the inorganic particles do not aggregate when mixed with the resin composition, and can be stably added, and further, the wettability of the resin and particles of the obtained cured product can also be improved.

[0077] Examples of the organic group contained in the silane coupling agent include vinyl, epoxy, styryl, methacryloxy, acryloxy, amino, urea, chloropropyl, mercapto, polysulfide, and isocyanate groups. The silane coupling agent may be used alone or in combination of two or more.

[0078] [Carboxyl-containing resin]

[0079] The curable resin composition of the present invention may contain a carboxyl group-containing resin as needed.

[0080] The carboxyl group-containing resin is a compound having a structure different from the above-mentioned (A) amideimide resin, and a resin having no amideimide structure and having a carboxyl group in the molecule can be used. Specific examples thereof include the following (E1) to (E10).

[0081] Specific examples of the non-photosensitive carboxyl group-containing resin include the following compounds (either oligomers or polymers).

[0082] (E1) Carboxyl group-containing resins obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, a lower alkyl (meth)acrylate, or isobutylene.

[0083] (E2) A carboxyl group-containing polyurethane resin obtained by the polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates, and carboxyl group-containing diol compounds such as dimethylol propionic acid and dimethylol butyric acid, and diol compounds such as compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups including polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, and bisphenol A-based alkylene oxide adduct diols.

[0084] (E3) A polyurethane resin containing terminal carboxyl groups obtained by reacting the ends of the polyurethane resin with an acid anhydride to obtain a polyurethane resin by polyaddition reaction of diisocyanate compounds such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, and diol compounds such as compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups including polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, and bisphenol A-based alkylene oxide adduct diols.

[0085] (E4) A carboxyl-containing photosensitive polyurethane resin obtained by the polyaddition reaction of a diisocyanate, a (meth)acrylate of a bifunctional epoxy resin such as a bisphenol A epoxy resin, a hydrogenated bisphenol A epoxy resin, a bisphenol F epoxy resin, a bisphenol S epoxy resin, a dimethylol epoxy resin, a biphenol epoxy resin or a partially anhydride-modified product thereof, a carboxyl-containing diol compound, and a diol compound.

[0086] (E5) A carboxyl group-containing photosensitive polyurethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule such as hydroxyalkyl (meth)acrylate to the synthesis of the resin of (E2) or (E4) to obtain a terminally (meth)acryloylated resin.

[0087] (E6) A carboxyl-containing photosensitive polyurethane resin which is terminally (meth)acryloylated by adding an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate or a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule during the synthesis of the resin of (E2) or (E4).

[0088] (E7) A carboxyl group-containing photosensitive resin obtained by reacting a bifunctional or higher-functional epoxy compound described below with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chains. The epoxy resin is preferably solid.

[0089] (E8) A carboxyl group-containing photosensitive resin obtained by reacting a polyfunctional epoxy compound obtained by epoxidizing the hydroxyl group of a bifunctional epoxy resin described below with epichlorohydrin with (meth)acrylic acid and adding a dibasic acid anhydride to the generated hydroxyl group. The epoxy resin is preferably solid.

[0090] (E9) A carboxyl group-containing photosensitive resin obtained by adding a cyclic ether such as ethylene oxide or a cyclic carbonate such as propylene carbonate to a polyfunctional phenol compound such as novolac, partially esterifying the obtained hydroxyl groups with (meth)acrylic acid, and reacting the remaining hydroxyl groups with a polyacid anhydride.

[0091] (E10) A carboxyl-containing photosensitive resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule such as glycidyl (meth)acrylate or α-methylglycidyl (meth)acrylate to the resins (E1) to (E9).

[0092] (E11) A compound having multiple phenolic hydroxyl groups in one molecule, i.e., a polyphenol compound (e.g., phenol novolac, cresol novolac) is reacted with an alkylene oxide such as ethylene oxide and propylene oxide, and the resulting reaction product such as a polyol resin is reacted with a monocarboxylic acid containing an unsaturated group such as (meth)acrylic acid, and the resulting reaction product is further reacted with a polyacid anhydride to obtain a carboxyl-containing photosensitive resin.

[0093] (E12) A carboxyl-containing photosensitive resin is obtained by reacting a polyphenol compound (e.g., phenol novolac, cresol novolac) with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, and reacting the resulting reaction product with a monocarboxylic acid containing an unsaturated group, and reacting the resulting reaction product with a polyacid anhydride.

[0094] In the present invention, it is preferable to use a carboxyl group-containing photosensitive resin having a polyphenol skeleton such as (E11) and (E12) described above.

[0095] The carboxyl group-containing resin may be used alone or in combination of two or more, but the total mass is preferably 1 part by mass or more and 40 parts by mass or less relative to 100 parts by mass of the solid content of the (A) amideimide resin, thereby increasing the solvents that can be selected in the curable resin composition and improving workability.

[0096] [Other ingredients]

[0097] In the curable resin composition of the present invention, other components other than the above components may be added within the range that does not impair the effects of the present invention. As additives, silicone-based or fluorine-based defoamers, leveling agents, thermal curing accelerators, thermal polymerization inhibitors, ultraviolet absorbers, solvents, silane coupling agents, plasticizers, foaming agents, flame retardants, antistatic agents, antioxidants, antibacterial / antifungal agents, etc. may be mixed.

[0098] It should be noted that a solvent may be used to form a viscosity suitable for coating the curable resin composition on a substrate or a carrier film. As such a solvent, an organic solvent is mainly used, and specific examples thereof include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, petroleum-based solvents, and the like. More specifically, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha, etc. Such organic solvents may be used alone or in combination of two or more.

[0099] The curable resin composition of the present invention may be a liquid type or a dry film type obtained by drying the liquid type resin composition. From the viewpoint of storage stability, the liquid type resin composition may be formed into a two-component type or a one-component type. Hereinafter, a dry film as a use mode of the curable resin composition is described in detail.

[0100] [Manufacturing of dry film]

[0101] The dry film of the present invention has a resin layer obtained by coating the curable resin composition of the present invention on a film (hereinafter also referred to as a "carrier film") and then drying it. For the dry film of the present invention, the curable resin composition of the present invention is diluted with an organic solvent to adjust to an appropriate viscosity, and is coated on a carrier film to a uniform thickness using a comma coater, a knife coater, a lip coater, a rod coater, an extrusion coater, a reverse coater, a transfer roll coater, a gravure coater, a spray coater, etc., and is usually dried at a temperature of 50 to 130° C. for 1 to 30 minutes to obtain. There is no particular restriction on the coating film thickness, and it can generally be appropriately set in the range of 3 to 100 μm, preferably 5 to 40 μm, based on the film thickness after drying.

[0102] As the carrier film, a plastic film can be suitably used, preferably a polyester film such as polyethylene terephthalate, a polyimide film, a polyamide-imide film, a polypropylene film, a polystyrene film, etc. The thickness of the carrier film is not particularly limited, and is generally selected within the range of 10 to 150 μm.

[0103] After the curable resin composition of the present invention is applied to a carrier film and dried, a removable film (hereinafter also referred to as "covering film") may be laminated on the surface of the coating film in order to prevent dust from adhering to the surface of the coating film. As the removable covering film, for example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a surface-treated paper, etc. may be used, as long as the adhesion between the coating film and the covering film is smaller than the adhesion between the coating film and the carrier film when the covering film is peeled off.

[0104] The curable resin composition of the present invention is applied onto a carrier film and then dried using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, or the like to obtain a dry film.

[0105] When the curable resin composition is directly applied to a substrate, as a substrate, in addition to printed circuit boards and flexible printed circuit boards with pre-formed circuits, there can also be mentioned: copper-clad laminates of all grades (FR-4, etc.), as well as polyimide films, PET films, glass substrates, ceramic substrates, wafer plates, etc. The copper-clad laminates use materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, and copper-clad laminates for high-frequency circuits using fluorine·polyethylene·polyphenylene ether (polyphenylene oxide)·cyanate esters, etc.

[0106] [Manufacturing of Cured Product]

[0107] The cured product (cured film) using the curable resin composition of the present invention is manufactured as follows. That is, first, the curable resin composition is diluted with a solvent as needed and then applied to a substrate. The coating of the curable resin composition is formed as follows: after the solvent is evaporated and dried, the obtained resin layer is heated to a temperature of about 100 to 180° C. for 30 to 60 minutes to form a cured coating.

[0108] As the coating method, any of dip coating, flow coating, bar coating, and screen printing can be applied.

[0109] The volatilization drying and heat curing after coating can be carried out using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, etc. (using a device with a heat source that uses steam to heat the air, a method of making the hot air in the dryer contact by convection, and a method of blowing it onto the support using a nozzle).

[0110] The curable resin composition of the present invention can make the light transmittance of the cured coating film with a film thickness of 20 μm obtained therefrom at a wavelength of 450 nm be 95% or more. Such excellent light transmittance is obtained by using the low molecular weight (A) amide-imide resin obtained from the above-mentioned specified raw materials in the curable resin composition of the present invention, and is particularly achieved by having an aliphatic structure. Thus, the cured coating film is visually recognized as colorless and transparent or a state close thereto.

[0111] In addition, according to the curable resin composition of the present invention, the residual stress of the cured coating obtained therefrom can be made lower than 25MPa. For the reduction of the residual stress of the cured coating, when the curable composition of the present invention particularly comprises carboxyl-containing resin, it is caused by the reaction of (B) thermosetting resin and carboxyl-containing resin. In addition, when the curable composition, except carboxyl-containing resin, also comprises epoxy compound as (B) curable resin, in the cured coating obtained by the curing reaction of the carboxyl of anhydride and epoxy group, the strength of the coating can be maintained and the residual stress can be relaxed.

[0112] The curable resin composition of the present invention can be used for electronic components. It should be noted that the present invention refers to components used in electronic circuits, including passive components such as resistors, capacitors, inductors, and connectors in addition to active components such as printed circuit boards, light-emitting diodes, and laser diodes, and the cured coating of the curable composition of the present invention exerts the effect of the present invention. The curable resin composition of the present invention is particularly suitable as an insulating cured film for forming a printed circuit board, and is further suitable for forming a permanent insulating film such as a covering layer, a solder mask, an interlayer insulating material, and an insulating material for forming a rewiring layer.

[0113] The electronic component including the cured product obtained from the curable resin composition of the present invention can fully exert its function as an electronic component because the cured product has excellent resolution and heat resistance. In addition, the cured product obtained from the curable resin composition of the present invention is also excellent in chemical resistance, so that during the cleaning using acid or alkali when manufacturing the substrate or the cleaning using solvent during installation, the electronic component is not deteriorated or deformed by the used chemicals, and the precision of the electronic component can be maintained or improved.

[0114] Example

[0115] Hereinafter, the present invention will be described in further detail based on Examples and Comparative Examples. The present invention is not limited to the following Examples, and all "parts" and "%" described below are based on mass unless otherwise specified.

[0116] [Synthesis of raw materials]

[0117] [Manufacture of amide-imide resin]

[0118] Synthesis Example 1: (A) Synthesis of amide-imide resin 1

[0119] In a flask equipped with a stirrer, a thermometer, and a condenser, 5184 g of EDGA (diethylene glycol monoethyl ether acetate), 2070 g (3 mol) of IPDI3N (isocyanurate-type triisocyanate synthesized from isophorone diisocyanate: NCO% = 18.2), and 1782 g (9 mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added, and the temperature was raised to 140°C. The reaction proceeded while foaming. The reaction was carried out at this temperature for 8 hours. The system became a light yellow liquid, and the characteristic absorption was measured by infrared spectroscopy. The result was 2270 cm-1, which is the characteristic absorption of the isocyanate group. -1 Completely disappeared at 1780cm -1 、1720cm -1 The absorption of the imide group was confirmed at the molten salt. The acid value was 140 KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of polystyrene conversion. In addition, the concentration of the resin component was 40% by mass. The solution of this resin was used as a solution of amide-imide resin 1.

[0120] Synthesis Example 2: Synthesis of (A') Amidoimide Resin 2

[0121] In a flask equipped with a stirrer, a thermometer, and a condenser, 4628 g of EDGA (diethylene glycol monoethyl ether acetate), 2070 g (3 mol) of IPDI3N (isocyanurate-type triisocyanate synthesized from isophorone diisocyanate: NCO% = 18.2), and 1386 g (7 mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added, and the temperature was raised to 140°C. The reaction proceeded while foaming. The reaction was carried out at this temperature for 8 hours. The system became a light yellow liquid, and the characteristic absorption was measured by infrared spectroscopy. The result was 2270 cm-1, which is the characteristic absorption of the isocyanate group. -1 Completely disappeared at 1780cm -1 、1720cm -1 The absorption of the imide group was confirmed at the urethane. The acid value was 140 KOHmg / g in terms of solid content, and the molecular weight was 5800 in terms of polystyrene conversion. In addition, the concentration of the resin component was 40% by mass. The solution of this resin was used as a solution of amide-imide resin 2.

[0122] Synthesis Example 3: (A") Synthesis of amide imide resin 3

[0123] In a flask equipped with a stirrer, a thermometer, and a condenser, 3554 g of EDGA (diethylene glycol monoethyl ether acetate), 2070 g (3 mol) of IPDI3N (isocyanurate-type triisocyanate synthesized from isophorone diisocyanate: NCO% = 18.2), and 1333 g (9 mol) of 1,2,4-benzenetricarboxylic acid 1,2-anhydride were added, and the temperature was raised to 140°C. The reaction proceeded while foaming. The reaction was carried out at this temperature for 8 hours. The system became a brown liquid, and the characteristic absorption was measured by infrared spectroscopy. The result was 2270 cm-1, which was the characteristic absorption of the isocyanate group. -1 Completely disappeared at 1780cm -1 、1720cm -1 The acid value was 140 KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of polystyrene-converted count average molecular weight. The concentration of the resin component was 40% by weight.

[0124] The solution of this resin is referred to as a solution of amideimide resin 3.

[0125] The number average molecular weights of the amideimide resins 1 and 2 were measured by gel permeation chromatography (GPC) (polystyrene standard) using the following measuring apparatus and measuring conditions.

[0126] Device name: Waters 2695

[0127] Detector: Waters 2414 differential refractive index (RI) detector

[0128] Column: Waters, HSPgel column for high speed analysis, HR MB-L,

[0129] 3μm, 6mm×150mm×2, and

[0130] Waters, HSPgel column, HR1, 3μm,

[0131] 6mm×150mm×2

[0132] Determination conditions:

[0133] Column temperature: 40°C

[0134] RI detector set temperature: 35°C

[0135] Developing solvent: tetrahydrofuran

[0136] Flow rate: 0.5mL / min

[0137] Sample volume: 10 μl

[0138] Sample concentration: 0.5wt%

[0139] Synthesis Example 4: Synthesis of carboxyl-containing resin

[0140] In an autoclave equipped with a thermometer, an alkylene oxide introduction device with a nitrogen introduction device, and a stirring device, 119.4 g of a novolac type cresol resin (manufactured by Showa Polymer Co., Ltd., trade name "Showa Novol CRG951", OH equivalent: 119.4), 1.19 g of potassium hydroxide, and 119.4 g of toluene were placed, and the system was replaced with nitrogen while stirring, and the temperature was raised. Then, 63.8 g of propylene oxide was slowly added dropwise, and the mixture was heated at 125 to 132°C and 0 to 4.8 kg / cm 2 The mixture was reacted for 16 hours at room temperature. After that, the mixture was cooled to room temperature, 1.56 g of 89% phosphoric acid was added to the reaction solution and mixed, and potassium hydroxide was neutralized to obtain a propylene oxide reaction solution of a novolac type cresol resin having a nonvolatile content of 62.1% and a hydroxyl value of 182.2 g / eq. This is obtained by adding an average of 1.08 mol of alkylene oxide to each equivalent of phenolic hydroxyl groups. 293.0 g of the obtained alkylene oxide reaction solution of a novolac type cresol resin, 43.2 g of acrylic acid, 11.53 g of methanesulfonic acid, 0.18 g of methylhydroquinone and 252.9 g of toluene were added to a reactor equipped with a stirrer, a thermometer and an air blowing tube, and air was blown in at a rate of 10 mL / min, and the mixture was reacted at 110°C for 12 hours while stirring. 12.6 g of water generated by the reaction was distilled as an azeotropic mixture with toluene. After that, the mixture was cooled to room temperature, and the obtained reaction solution was neutralized with 35.35 g of 15% sodium hydroxide aqueous solution, and then washed with water. After that, in an evaporator, toluene was replaced with 118.1 g of diethylene glycol monoethyl ether acetate and distilled off to obtain a novolac type acrylate resin solution. Next, 332.5 g of the obtained novolac type acrylate resin solution and 1.22 g of triphenylphosphine were added to a reactor equipped with a stirrer, a thermometer and an air blowing tube, and air was blown in at a rate of 10 mL / min. While stirring, 60.8 g of tetrahydrophthalic anhydride was slowly added, and the mixture was reacted at 95-101°C for 6 hours. A carboxyl-containing resin having an acid value of 88 mgKOH / g and a solid content of 71% was obtained.

[0141] [Examples 1 to 5 and Comparative Examples 1 to 5]

[0142] [Preparation of curable resin composition]

[0143] Each component was blended as described in Table 1, pre-mixed in a stirrer, and then kneaded and dispersed using a three-roll mill to prepare curable resin compositions of Examples and Comparative Examples.

[0144] In addition, the compounding quantity in a table|surface shows mass part (solid content conversion).

[0145] <1. Heat resistance>

[0146] The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied to a carrier film (polyethylene terephthalate film). It was heated and dried in a hot air dryer at 80°C for 30 minutes to form a curable resin composition layer with a thickness of 20 μm, and a covering film (polypropylene film) was attached to the coating to obtain a dry film. After that, the covering film was peeled off, hot-laminated on a copper foil, and heated at 180°C for 60 minutes to cure it. The cured coating was peeled off from the obtained copper foil with a cured coating to obtain a cured coating.

[0147] The glass transition temperature of the obtained cured coating film was measured under the following conditions.

[0148] Apparatus: Dynamic viscoelasticity measuring apparatus (DMA6100 manufactured by Seiko Instruments Inc.)

[0149] Measuring temperature: 30~300℃(5℃ / min)

[0150] Frequency: 1Hz

[0151] Glass transition temperature: The maximum value of tan δ measured was taken as the glass transition temperature.

[0152] The higher the glass transition temperature, the more elastic changes occur at high temperatures, and therefore, it is judged that the heat resistance is high.

[0153] The evaluation criteria are as follows.

[0154] ◎:Above 190℃

[0155] 〇:Above 180℃

[0156] △:Above 170℃

[0157] ×: below 170℃

[0158] <2. Residual stress and wafer warpage>

[0159] The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied on a carrier film (polyethylene terephthalate film). It was heated and dried in a hot air dryer at 80°C for 30 minutes to form a curable resin composition layer with a thickness of 10 μm, and a cover film (polypropylene film) was attached to the coating film to obtain a dry film.

[0160] On the other hand, the initial warpage (average radius of curvature), elastic modulus, thickness, and Poisson's ratio of a simulated silicon wafer used as a substrate were measured in advance.

[0161] The dry film (1 layer) obtained in each example was thermally laminated on the above wafer at a maximum temperature of 100° C. using a laminator, and then heated at 180° C. for 60 minutes to cure.

[0162] Thus, a cured coating film was formed on the wafer. The warpage (average radius of curvature) of the wafer obtained in this way was measured.

[0163] The average radius of curvature, elastic modulus, thickness, and Poisson's ratio were measured using a thin film test measuring apparatus FLX-2320-S manufactured by Toho Technology Corporation.

[0164] The residual stress was calculated by the following formula.

[0165] Residual stress = {wafer elastic modulus × (wafer thickness) 2 / (1-Poisson's ratio of wafer)×6×thickness of cured coating}×{1 / radius of curvature of wafer after formation of cured coating-1 / radius of initial wafer curvature}

[0166] <3.Laminability>

[0167] The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied to a carrier film (polyethylene terephthalate film). It was heated and dried in a hot air dryer at 80°C for 30 minutes to form a curable resin composition layer with a thickness of 30 μm, and a cover film (polypropylene film) was attached to the coating film to obtain a dry film (film thickness 15 μm).

[0168] For a double-sided printed circuit board with a fine circuit having a comb-tooth pattern and a copper thickness of 10 μm, L (line width: wiring width) / S (line spacing: spacing width) = 5 / 5 μm, and an aspect ratio of 2.0, an etching treatment equivalent to 0.5 μm was performed using CZ-8101 made by MEC as a pretreatment. Then, the 15 μm thick dry film prepared in the above was laminated on the double-sided printed circuit board having L / S formed thereon using an intermittent vacuum pressure laminator MVLP-500 (made by Meiki Co., Ltd.). The lamination conditions were 5 kgf / cm 2 , 100°C, 1 minute, 1 Torr, and then in the hot plate press process, 10 kgf / cm 2 , 100℃, 1 minute conditions for leveling.

[0169] After lamination, air entered the boundary between the line width and the line spacing, and after peeling the carrier film, the presence of bubbles (voids) was visually confirmed.

[0170] A: No voids were found.

[0171] B: Holes were confirmed in several places.

[0172] C: The viscosity and elastic modulus were high, and the bottom surface of the line spacing of the evaluation substrate after lamination was not in contact with the resin layer of the dry film.

[0173] <4. Transmittance>

[0174] The curable resin composition is diluted with methyl ethyl ketone to an appropriate viscosity and applied to a glass substrate. It is heated and dried in a hot air dryer at 80°C for 30 minutes to form a curable resin composition layer with a thickness of 20 μm, and heated at 180°C for 60 minutes to cure it. The transmittance is measured using a UV / VIS spectrophotometer, and a glass substrate without a cured coating is used as a basis to measure the transmittance at 450nm of a glass substrate with a cured coating. Here, the transmittance is evaluated using an ultraviolet-visible spectrophotometer (Ubest-V-570DS manufactured by JASCO Corporation) and an integrating sphere device (ISN-470 manufactured by JASCO Corporation) in accordance with ISO 13468.

[0175] The evaluation criteria are as follows.

[0176] A: Transmittance is more than 98%

[0177] B: Transmittance is 95% or more and less than 98%

[0178] C: Transmittance is 90% or more and less than 95%

[0179] D: Transmittance less than 90%

[0180] [Table 1]

[0181] Ingredients (solid ingredients only) Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 (A) Amidoimide resin 1 100 80 100 100 100 (A') amide imide resin 2 100 80 (A'') amide imide resin 3 100 (B) Thermosetting resin 1 40 40 40 40 40 40 40 (B) Thermosetting resin 2 40 40 40 (C) Thermal curing accelerator 1 1 1 1 1 1 1 1 1 1 (C) Thermal curing accelerator 2 1 (D) Inorganic particles 1 50 50 50 50 50 50 50 50 (D) Inorganic particles 2 50 50 Carboxyl resin 20 20 100 Phenolic resin 100 Heat resistance(℃) 200 181 198 200 205 200 180 205 165 150 Heat resistance (evaluation criteria) ◎ 〇 ◎ ◎ ◎ ◎ 〇 ◎ × × Residual stress (MPa) 19.9 17.8 19.8 18.9 22.0 20.2 19.5 20.0 28.0 20.5 Wafer warpage (μm) 79 55 80 63 82 80 74 80 210 81 Lamination A A A A A C B A B A 400nm transmittance A B A A A A B C D C

[0182] * The compounding amounts in the table are based on parts by mass.

[0183] The details of the materials described in the table are shown below.

[0184] Amidoimide resin 1: synthesized from Synthesis Example 1 Mn = 800

[0185] Amidoimide resin 2: synthesized from Synthesis Example 2 Mn = 5800

[0186] Amidoimide resin 3: synthesized from Synthesis Example 3 Mn = 800

[0187] Thermosetting resin 1: Biphenyl-modified epoxy resin (NC-3000, manufactured by Nippon Kayaku Co., Ltd.)

[0188] Thermosetting resin 2: Epoxy resin containing a dicyclopentadiene skeleton (EPICLON (registered trademark) HP7200, manufactured by DIC Corporation)

[0189] Thermal curing accelerator 1: imidazole curing agent (Curezol 2MZ-A (manufactured by Shikoku Chemicals Co., Ltd.)

[0190] Thermal curing accelerator 2: 2-ethyl-4-methylimidazole (Curezol 2E4MZ (manufactured by Shikoku Chemicals Co., Ltd.)

[0191] Inorganic particles 1: Barium sulfate Sakai Chemical BF-10 (particle size: 100nm)

[0192] Inorganic particles 2: Silica Nippon Catalyst Seahostar S10 (particle size: 100nm)

[0193] Carboxyl-containing resin: Synthesized in Synthesis Example 4

[0194] Phenolic resin: Phenol novolac resin HF-1H

[0195] (Made by Meiwa Chemicals Co., Ltd., hydroxyl value 105-109 g / eq, solid content 65%)

[0196] As described above, the curable resin composition of the present invention not only has excellent heat resistance but also has low residual stress, is less likely to cause wafer warping, has good lamination properties, and further, has good light transmittance.

[0197] The present invention is not limited to the configuration and examples of the above-described embodiments, and various modifications can be made within the scope of the gist of the invention.

Claims

1. A curable resin composition, characterized in that Include: (A) amide-imide resin, (B) Thermosetting resin, (C) thermal curing accelerator, (D) Inorganic particles, and A carboxyl-containing resin having no amide-imide structure and having a carboxyl group in the molecule, The (A) amide-imide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 900. The (B) thermosetting resin is an epoxy compound having a biphenyl skeleton, an epoxy compound having a dicyclopentadienyl skeleton, or a mixture thereof. The average particle size of the inorganic particles (D) is 100 nm or less, The content of the (D) inorganic particles is 10 to 50% by mass based on the total mass of the solid content of the curable resin composition, and The curable resin composition has a light transmittance of 95% or more at 450 nm when formed into a cured coating film having a film thickness of 20 μm.

2. The curable resin composition according to claim 1, characterized in that The residual stress of the cured coating film is less than 25 MPa.

3. A dry film, characterized in that: A resin layer comprising the curable resin composition according to claim 1 or 2. 4 . A cured product obtained by curing the curable resin composition according to claim 1 or 2 or the resin layer of the dry film according to claim 3 . 5 . An electronic component comprising the cured product according to claim 4 .

Citation Information

Patent Citations

  • Curable resin composition

    JP2001226464A

  • Alcohol-modified polyamide-imide resin and process for producing same

    CN109312045A